2009
DOI: 10.1016/j.annemergmed.2009.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Asynchronous Physician Voicemail Sign-out for Emergency Department Admissions

Abstract: Background-Communication failures contribute to errors in the transfer of patients from the emergency department (ED) to inpatient medicine units. Oral (synchronous) communication has numerous benefits but is costly and time-consuming. Taped (asynchronous) communication may be more reliable and efficient, but lacks interaction. We evaluated a new asynchronous physicianphysician sign-out compared to the traditional synchronous sign-out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
1
28
0
1
Order By: Relevance
“…As a result, the primary team physicians and on-call physicians worked together to build a good representation of the patient. The result is consistent with a study by Horwitz et al (22) Despite the advantage of synchronous feedback, the present study revealed that systemic information loss occurred in pure verbal communication. This was observed when on-call physicians transferred verbally delivered information into written notes.…”
Section: Note For Patients Otherssupporting
confidence: 83%
“…As a result, the primary team physicians and on-call physicians worked together to build a good representation of the patient. The result is consistent with a study by Horwitz et al (22) Despite the advantage of synchronous feedback, the present study revealed that systemic information loss occurred in pure verbal communication. This was observed when on-call physicians transferred verbally delivered information into written notes.…”
Section: Note For Patients Otherssupporting
confidence: 83%
“…Improvements in information transfer were the most commonly reported successes, being found in more than half of the studies examining this,20 24 25 28 29 32 33 37 38 43–45 and staff satisfaction was the next most commonly improved in 35% of studies28–32 34 35 43–46—a similar proportion to those reporting improvements in time taken and compliance with protocols. Of studies which attempted to evaluate changes in patient outcome, only two35 40 of 1019 21 22 30 32 35 36 40 41 47 studies reported a significant benefit with one study reporting a 12% decrease in adverse events (need for cardiopulmonary recussitation (CPR), extracorporeal membrane oxygenation (ECMO) and acidosis) (p=<0.001)35 and the other study reporting a significant reduction in length of stay (p=0.047) 40. There was no obvious difference between the success rates of multi and mono-component interventions, and none of our defined categories (standardisation tools, team training approaches or quality improvement programmes) seemed to be clearly associated with a better chance of a positive outcome.…”
Section: Resultsmentioning
confidence: 99%
“…17 Another example of handoff occurs in the transition from emergency to inpatient care, which might be associated with adverse events, and is a known vulnerable area for the processes of handoff. 18,19 An important type of handoff not studied extensively, however, occurs during service change or when a group of clinicians switch entirely. At training institutions, residents alternate through different rotations on a set schedule (often monthly).…”
mentioning
confidence: 99%